Are aflatoxins a One Health issue? Results and insights from studies on aflatoxins in the East African dairy value chains - Lindahl, Johanna F.; Senerwa, D.M.; Mwangi, G.; Sirma, A.J.; Atherstone, Christine; Grace, Delia (2016)
Aflatoxins are toxic byproducts from some Aspergillus fungi, mainly Aspergillus flavus, colonizing crops before and after harvest, with preference for maize and groundnuts. In large quantities the toxins are mainly hepatotoxic, and can cause death due to liver failure. Chronic low-dose exposure has been shown to cause immunosuppression and reduced growth in animals, and has been associated with stunting in children. Aflatoxin B1 is one of the most potent natural carcinogens known, causing hepatocellular carcinoma. When animals consume aflatoxins they may have clinical symptoms, reduced productivity and performance, but our literature review suggest that there is still knowledge gaps as to how much animals are affected. In addition, aflatoxins are metabolized by the animals, and residues may persist in low levels in meat and eggs, but around 7-10% of what a dairy cow consumed is excreted as the metabolite aflatoxin M1 into the milk. Our research from Kenya show that milk may contain 140 times WHO recommended levels, and feed samples may contain almost 2000 times the legal levels in Kenya. In some of the studied villages, 100% of samples exceeded legal limits. In addition, our study on urban children shows high rates of stunting in low-income areas, and an association with the consumption of aflatoxin M1. Thus, aflatoxins are a problem affecting both humans and animals, where animals do contribute to the risks for humans, but we also discuss around the potential of animals acting as a solution for the problem as well, discussing policies and mitigation methods.